A common variant in the FTO gene is associated with body mass index in males and postmenopausal females but not in premenopausal females. Czech post-MONICA and 3PMFs studies - Hubacek, Jaroslav A; Pitha, Jan; Adamkova, Vera; Lanska, Vera; Poledne, Rudolf (Clinical chemistry and laboratory medicine, 2009)
BACKGROUND: Recently, the role of the FTO (fat mass and obesity associated) gene in obesity development was described in Western European, but not in Oceanic, cohorts. The objective of this study was to test the hypothesis that the FTO single nucleotide polymorphism (SNP) is associated with body mass index (BMI) in the Slavic population and to analyze if there could be sex-specific effects of the SNP on BMI, waist-to-hip ratio (WHR), and lipid parameters. METHODS: We analyzed three large population-based samples comprising the post-MONICA study (1191 males, 1368 females) and the 3PMFs study (908 females). RESULTS: FTO rs17817449 SNP was related to BMI in males (p=0.014). In the females from both the post-MONICA and the 3PMFs study, FTO had no effect on BMI. Sub-analysis of females from the 3PMFs study demonstrated that FTO had an effect on BMI in postmenopausal females (p=0.035) but not in premenopausal females (follicle-stimulating hormone <40 U/L was used as marker of premenopausal status). WHR and lipid parameters were not associated with FTO in any of the analyzed groups. CONCLUSIONS: These results suggest that the effect of FTO SNP rs17817449 may be, in some populations at least, restricted to males and postmenopausal females.
Keywords: gen pro FTO; proteiny; Proteins; Male; Premenopause; postmenopauza; Česká republika; Adult; Aged; dospělí; mužské pohlaví; senioři; jednonukleotidový polymorfismus; premenopauza; Czech Republic; Postmenopause; Alpha-Ketoglutarate-Dependent Dioxygenase FTO; Polymorphism, Single Nucleotide; lidé; ženské pohlaví; Humans; Body Mass Index; index tělesné hmotnosti; Female; lidé středního věku; Middle Aged